Blended Learning Environments for Adults 2012
DOI: 10.4018/978-1-4666-0939-6.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Rationale for Designing a Blended Learning Teachers’ Professional Development Program

Abstract: This chapter explores the underlying theoretical principles that provided the basis for the design and implementation of a professional development program for informatics teachers in Greece. A blended learning model was adopted combining live workshop meetings, face-to-face in-lab training sessions and online videoconferencing sessions. The framework of constructivism and experiential learning was used as a theoretical rationale for the combination of face-to-face activities with online learning experiences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In support of integrating technology into teacher education, Dziuban et al (2018) noted that blended learning provides opportunities by interacting with almost every aspect of higher education, and because of its flexibility, it allows for maximizing positive education functions. Several studies investigated the effectiveness of blended learning situations in teacher education (Fuchs, 2010;Mouzakis et al, 2012;Zagouras et al, 2022). Huhn (2012) noted that one of the characteristics of a successful and encouraging foreign language teacher education program is giving teacher candidates the chance to participate in technology-enhanced instruction.…”
Section: Discussionmentioning
confidence: 99%
“…In support of integrating technology into teacher education, Dziuban et al (2018) noted that blended learning provides opportunities by interacting with almost every aspect of higher education, and because of its flexibility, it allows for maximizing positive education functions. Several studies investigated the effectiveness of blended learning situations in teacher education (Fuchs, 2010;Mouzakis et al, 2012;Zagouras et al, 2022). Huhn (2012) noted that one of the characteristics of a successful and encouraging foreign language teacher education program is giving teacher candidates the chance to participate in technology-enhanced instruction.…”
Section: Discussionmentioning
confidence: 99%
“…It was also indicated that the combination of different training models (in-labs and on-line training, workshops etc. ), was perceived as a challenging innovation by teachers and attracted their interest (Mouzakis et al, 2012). Moreover, specific issues and difficulties have been met for the design of a blended learning model for teacher training on ICT (Dagdilelis, 2014).…”
Section: Related Workmentioning
confidence: 99%